Nutritional deficiency in "umbuzeiro" seedlings caused by the omission of macronutrients - Gonçalves, Francisco César; Neves, Orlando Sílvio Caires; Carvalho, Janice Guedes de (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the growth and the visual symptoms of macronutrients deficiency in "umbuzeiro" seedlings (Spondias tuberosa) cultivated on complete nutritive solution and on solution with individual omission of N, P, K, Ca, Mg and S. The absences of Ca, N, Mg and K caused a reduction in seedling growth. The omission of individual macronutrients conducted to morphological disorders related to the nutritional deficiency. A higher requirement of N, K, Ca and Mg is observed during the initial phase of the growth, and the reduction in total dry matter follows the order: Ca > N > K > Mg > S > P.